An annotated checklist of the fossil birds of Australia. Issue 1 (2nd January 2020) - Worthy, Trevor H.; Nguyen, Jacqueline M. T.
ABSTRACT: A complete annotated checklist of all species of birds based on fossil material known as of 2019 from continental Australia is presented. Taxa range from Cretaceous to Holocene in age. It includes synonyms with full bibliographic details and specifics of the type material in all cases, such as specimen or locality data, source local fauna and geological age. Nomina based on fossil material that are now synonymised under extant taxa are also included. The list includes 95 avian species, of which 78 are extinct, in 66 genera. Five extinct subspecies in modern genera are recognised. These species represent 33 family- and 19 ordinal-group taxa, or nearly half of modern avian orders.